2017
DOI: 10.1371/journal.pone.0175456
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-resistant infections among postpartum women at a Ugandan referral hospital

Abstract: IntroductionPuerperal sepsis causes 10% of maternal deaths in Africa, but prospective studies on incidence, microbiology and antimicrobial resistance are lacking.MethodsWe performed a prospective cohort study of 4,231 Ugandan women presenting to a regional referral hospital for delivery or postpartum care, measured vital signs after delivery, performed structured physical exam, symptom questionnaire, and microbiologic evaluation of febrile and hypothermic women. Malaria rapid diagnostic testing, blood and urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 31 publications
6
70
1
3
Order By: Relevance
“… Acquisition: All studies reported pregnant women with community‐acquired infections, except one study where three‐fourth of UTIs among postpartum patients were described as catheter‐associated UTIs. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Acquisition: All studies reported pregnant women with community‐acquired infections, except one study where three‐fourth of UTIs among postpartum patients were described as catheter‐associated UTIs. …”
Section: Resultsmentioning
confidence: 99%
“…Four studies did not report the frequency of specific ESBL-P organisms. 24,29,41,45 The remaining studies reported a total of 1448 Enterobacteriaceae strains cultured and identified as ESBL producers. The most commonly reported organisms were E coli with a pooled prevalence of 61% (47, 74%) and K pneumoniae with a prevalence of 40% (22, 57%).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, after Cesarean section women are treated with combination intravenous ceftriaxone and metronidazole for three days, followed by five days of oral cefixime. Microbiological evaluation of potential infections is not routine, but when requested, samples are processed at MUST's teaching lab adjacent to MRRH [15]. For this study, wound sepsis was defined by a positive culture of fluid or tissue from the superficial incision for microorganisms.…”
Section: Study Setting and Designmentioning
confidence: 99%